Hemoptysis due to Pulmonary Arteriovenous Malformation after Coil Embolization during Long-Term Follow-Up. (20th October 2019) - Shimohira, Masashi; Iwata, Kenji; Ohta, Kengo; Sawada, Yusuke; Hashimoto, Takeshi; Okuda, Katsuhiro; Nakanishi, Ryoichi; Shibamoto, Yuta
Abstract : A 28-year-old man with a history of coil embolization of multiple pulmonary arteriovenous malformations presented with hemoptysis 11 years after initial embolization. A cavity lesion in the left upper lobe, which was accompanied by deformed coils and ground-glass opacity, was considered responsible for hemoptysis. Embolization of the bronchial artery was performed.